Collective and convective effects compete in patterns of dissolving surface droplets. Issue 26 (8th June 2016) - Laghezza, Gianluca; Dietrich, Erik; Yeomans, Julia M.; Ledesma-Aguilar, Rodrigo; Kooij, E. Stefan; Zandvliet, Harold J. W.; Lohse, Detlef
Abstract : The effects of neighboring droplets on the dissolution of a sessile droplet, i.e. collective effects, are investigated both experimentally and numerically. Abstract : The effects of neighboring droplets on the dissolution of a sessile droplet, i.e. collective effects, are investigated both experimentally and numerically. On the experimental side small approximately 20 nL mono-disperse surface droplets arranged in an ordered pattern were dissolved and their size evolution is studied optically. The droplet dissolution time was studied for various droplet patterns. On the numerical side, lattice-Boltzmann simulations were performed. Both simulations and experiments show that the dissolution time of a droplet placed in the center of a pattern can increase by as much as 60% as compared to a single, isolated droplet, due to the shielding effect of the neighboring droplets. However, the experiments also show that neighboring droplets enhance the buoyancy driven convective flow of the bulk, increasing the mass exchange and counteracting collective effects. We show that this enhanced convection can reduce the dissolution time of droplets at the edges of the pattern to values below that of a single, isolated droplet.